More than "male" and "female": the role of gender identity in white-collar offending intentions - Reed, Shon M. (Crime, law and social change, 2023)
The gender gap in white-collar crime perpetration is well-established, yet reasons for women’s underrepresentation among this offending group remain disputed. Specifically, scholars debate whether women are socialized against offending or whether they simply lack the opportunity to engage in these types of crime. The current study focuses on the socialization perspective, looking beyond one’s gender assigned at birth and instead looking at gender identity, threats to that identity, and the interaction of race and gender identity. Using an online, experimental vignette design depicting embezzlement, we find that gender identity influences the likelihood of crime perpetration even when one’s opportunity to commit crime is held constant. Future directions for research and theoretical development into gender and white-collar crime are discussed following a presentation of the results.